2017
DOI: 10.1002/mc.22710
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA‐135b and microRNA‐182 promotes chemoresistance of colorectal cancer by targeting ST6GALNAC2 via PI3K/AKT pathway

Abstract: MicroRNAs (miRNAs) are increasingly involved in the development of drug resistance, including 5-fluorouracil (5-FU) resistance in colorectal cancer (CRC). Aberrant sialylation is correlated with human CRC. The study was to explore whether miR-135b and miR-182 modulated 5-FU chemoresistance of CRC by targeting ST6GALNAC2 via PI3K/AKT pathway. MiR-135b and miR-182 were found to be up-regulated in CRC tissues and 5-FU resistant CRC cell lines. Forced miR-135b and miR-182 expression also affected ST6GALNAC2 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…WNT/β-catenin, RAS/ERK/ MAPK, JAK/STAT, NOTCH), we believe ncRNA may also play a role in the resistance of PI3K inhibitors [194][195][196][197][198][199]. Not surprisingly, more and more researches have suggested that deviant ncRNA expression is powerfully concerned about tumor drug resistance [200][201][202][203][204][205][206][207][208]. Recent studies have indicated potential mechanism of acquired resistance to dual PI3K/mTOR inhibitors, including elevated glycolysis accompanied with depletion of mitochondrial DNA, and upregulated DNA methyltransferases which Reduce PTEN and PPP2R2B expression [209,210].…”
Section: Resistancesmentioning
confidence: 99%
“…WNT/β-catenin, RAS/ERK/ MAPK, JAK/STAT, NOTCH), we believe ncRNA may also play a role in the resistance of PI3K inhibitors [194][195][196][197][198][199]. Not surprisingly, more and more researches have suggested that deviant ncRNA expression is powerfully concerned about tumor drug resistance [200][201][202][203][204][205][206][207][208]. Recent studies have indicated potential mechanism of acquired resistance to dual PI3K/mTOR inhibitors, including elevated glycolysis accompanied with depletion of mitochondrial DNA, and upregulated DNA methyltransferases which Reduce PTEN and PPP2R2B expression [209,210].…”
Section: Resistancesmentioning
confidence: 99%
“…A previous study focused on miR-135b, miR-182 and the PI3K/AKT signaling pathway in colorectal cancer (CRC), identifying that overexpressed miR-182 promotes the chemoresistance of CRC by targeting ST6 N-acetylgalactosaminide α-2,6-sialyltransferase 2 via the PI3K/AKT signaling pathway (42). Furthermore, the ability of miR-182 to activate the PI3K/AKT signaling pathway has previously been confirmed (31). These findings indicated that inhibition of miR-182 suppressed cell viability and invasion via the activation of CADM2 and by suppressing the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, another study identified that miR-182 overexpression is associated with VEGF-A production and angiogenesis (34). Liu et al (31) suggested that inhibition of miR-182 decreases the level of phosphorylated-AKT. MVD is used to measure angiogenesis, and it has been reported that enhanced angiogenesis appears in miR-182-overexpressing cells (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that miR-135b is an important oncogenic effector in cancers. Moreover, some studies suggest that miR-135b acts as a contributor to anti-apoptosis and chemoresistance in CRC [40,41]. However, the potential mechanisms are required to be explored.…”
Section: Discussionmentioning
confidence: 99%